Storyboard design course : principles, practice, and techniques : the ultimate guide for artists, directors, producers, and scriptwriters - Cristiano, Giuseppe (Hauppauge, NY : Barron's, 2007)
From the Publisher: Storyboards are the blueprint for a multitude of media productions, including TV shows, movies, commercials, music videos, computer games, and animation. A critical part of the creative process, they can be used to pitch an idea, communicate a concept, help build a budget, and execute an entire shoot. This book is the ultimate storyboard manual, packed with fully-finished art and work-in progress examples from students and industry professionals. As well as being an essential guide for aspiring storyboard artists, this comprehensive book will enable anyone working in media production to get the most out of both the storyboard artist and the storyboard process. Learn how to develop sketching skills, adapt styles, get inspiration, and interpret a script or a brief with help from these practical tutorials and interactive exercises. Understand the language of storyboards and the limitations and conventions of different mediums. Build scenes, plan shot sequences, and understand the importance of composition, framing, and continuity. Set up your own work space and get advice on entering the world of professional storyboard artists.
"A Quarto book"--T.p. verso.
Includes bibliographical references (pages 182-183) and index.
Keywords: Storyboards; Commercial art -- Technique